Depression in systemic lupus erythematosus: A manifestation of microcirculation dysfunction?. (May 2023) - Koletsos, Nikolaos; Dipla, Konstantina; Triantafyllou, Areti; Dolgyras, Panagiotis; Aslanidis, Spyros; Zafeiridis, Andreas; Galanopoulou, Vasiliki; Douma, Stella; Gkaliagkousi, Eugenia
Objectives: Depression is highly prevalent among systemic lupus erythematosus (SLE) patients. Brain hypoperfusion in neuropsychiatric SLE patients might be associated with emotional difficulties. However, no previous study examined possible associations of depression with brain oxygenation during a mild physical stress in non-neuropsychiatric SLE patients. Our study aimed to identify possible differences in cerebral oxygenation during exercise in SLE patients with and without depressive symptoms using near-infrared spectroscopy (NIRS) and examine possible underlying mechanisms through evaluation of vascular cell adhesion molecule 1 (VCAM-1) levels. Methods: SLE patients without a known neuropsychiatric history or treatment with antidepressants or antipsychotic drugs were enrolled. Participants were assigned into groups based on Beck's Depression Inventory I (BDI-I). Patients with BDI-I score ≥10 comprised the SLE-depression group and those with BDI-I score <9 the SLE-non-depression group. All participants underwent a protocol involving a seated rest, a 3-min handgrip exercise (at 30% of maximal strength), and a 3-min recovery. NIRS was used to monitor changes in cerebral oxygenated hemoglobin (O2Hb), deoxygenated (HHb), and total hemoglobin (tHb). VCAM-1 levels were measured in serum samples. Results: Twenty-three patients were enrolled. During exercise, the SLE-depression group exhibited a significantly lower increase in cerebral O2Hb [(peak-O2Hb ( p = 0.039); O2Hb-area under the curve, AUC, p = 0.027) vs. SLE-non-depression group. BDI-I score was inversely correlated with AUC (rho = −0.493, p = 0.017) and positively correlated with VCAM-1 levels (rho = 0.501, p = 0.034). Conclusion: This study suggests a possible association between emotional abnormalities and microvascular impairment (cerebral oxygenation and endothelial dysfunction) in SLE However, larger studies are needed to confirm these results.